2019
DOI: 10.1038/s41467-019-09277-9
|View full text |Cite
|
Sign up to set email alerts
|

A GPX4-dependent cancer cell state underlies the clear-cell morphology and confers sensitivity to ferroptosis

Abstract: Clear-cell carcinomas (CCCs) are a histological group of highly aggressive malignancies commonly originating in the kidney and ovary. CCCs are distinguished by aberrant lipid and glycogen accumulation and are refractory to a broad range of anti-cancer therapies. Here we identify an intrinsic vulnerability to ferroptosis associated with the unique metabolic state in CCCs. This vulnerability transcends lineage and genetic landscape, and can be exploited by inhibiting glutathione peroxidase 4 (GPX4) with small-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
465
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(496 citation statements)
references
References 68 publications
11
465
0
Order By: Relevance
“…4B) either alone or in combination with FG4592. This data is consistent with a recent work, that suggest that HIF-2α-dependent lipid alterations increase ferroptotic cell death in renal cancer derived cell lines 31 . We analyzed the expression of two lipid genes important in ferroptosis sensitization in renal cancers, hypoxia inducible lipid droplet associated protein (HILPDA) and perilipin 2 (PLIN2).…”
Section: Drug Screen Identifies Synthetic Vulnerability To Hif2 In Tsupporting
confidence: 93%
See 2 more Smart Citations
“…4B) either alone or in combination with FG4592. This data is consistent with a recent work, that suggest that HIF-2α-dependent lipid alterations increase ferroptotic cell death in renal cancer derived cell lines 31 . We analyzed the expression of two lipid genes important in ferroptosis sensitization in renal cancers, hypoxia inducible lipid droplet associated protein (HILPDA) and perilipin 2 (PLIN2).…”
Section: Drug Screen Identifies Synthetic Vulnerability To Hif2 In Tsupporting
confidence: 93%
“…We also observe the similar effect in a panel of CRC cell lines, where either the growth inhibition or lipid ROS production by erastin or RSL3 was significantly increased by pre-treating the cells with a hypoxia mimetic. In a recent study HIF-2α has been shown to be driving vulnerability to RSL3-induced ferroptosis in clear-cell renal cell carcinoma (ccRCC) 31 . Our results also show a similar mechanism in colon cancer cells, where HIF-2α deficient CRC cells are completely resistant to high concentrations of erastin or RSL3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we examined the possibility that GOT1 could be altering phospholipid composition. HIF-2α stabilization has been recently shown to promote a ferroptosis primed cell-state by selectively enriching for polyunsaturated acids in clear-cell carcinomas 38 . This vulnerability was mediated by hypoxia-inducible lipid droplet-associated protein (HILPDA).…”
Section: Resultsmentioning
confidence: 99%
“…This seems plausible since recent studies have elucidated that ROS generated by SOD2 silencing increases HIF1α expression . Just recently, the role of glutathione peroxidase 4 (GPX4), which uses glutathione to selectively detoxify lipid hydroperoxides and acts as a gatekeeper for ferroptosis, an iron‐dependent cell‐death pathway, has been highlighted in clear cell carcinomas, including clear cell RCC . Namely, due to intensified lipid and glycogen synthesis and accumulation, these carcinomas develop intrinsic vulnerability to ferroptosis.…”
Section: Altered Redox Homeostasis Underlying Rccmentioning
confidence: 99%